The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/15257770.2011.569810
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Bulged Nucleotides in Hybrids Formed by Rna and Imidazole-Derivatized Oligo-2′-O-Methylribonucleotides

Abstract: In order to enhance the efficacy of small antisense molecules, we examined a series of antisense oligonucleotides derivatized with functional groups designed to enable them to hydrolyze their RNA target. Solid phase synthetic methods were used to prepare imidazole-derivatized antisense oligo-2′-O-methylribonucleotides. Upon binding, these oligonucleotides create internal bulged bases in the target RNA that serve as sites for hydrolysis. We observed that an oligonucleotide derivatized with a side chain containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…ATM null status was confirmed by phosphorylation assays (May 2009). Adhered cells were irradiated using an Eldorado 8 60 Co teletherapy unit (Theratronics International Ltd) at dose rates between 150 and 180 cGy/min 1 hour before collection, or with 20 J/m 2 of UVB light at 254 nm 1 hour before collection [14] . Cells were treated with 100 µM Etoposide (Sigma-Aldrich) or 50 µM H 2 O 2 (Fisher) 1 hour before collection.…”
Section: Methodsmentioning
confidence: 99%
“…ATM null status was confirmed by phosphorylation assays (May 2009). Adhered cells were irradiated using an Eldorado 8 60 Co teletherapy unit (Theratronics International Ltd) at dose rates between 150 and 180 cGy/min 1 hour before collection, or with 20 J/m 2 of UVB light at 254 nm 1 hour before collection [14] . Cells were treated with 100 µM Etoposide (Sigma-Aldrich) or 50 µM H 2 O 2 (Fisher) 1 hour before collection.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that RNA bulge loop region of an RNA/DNA duplex is susceptible to hydrolysis [10,15,18,19]. We first tested five DNA sequences (DNA 2 , 3 , 4 , 5 and 6 ) for their impact on RNA cleavage rate.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, imidazole, which has been widely used in the design of artificial ribonucleases, showed very low cleaving activity (< 1%). Many artificial ribonucleases as well as the natural RNase A contain a pair of imidazoles to function cooperatively [ 10 , 11 ]. The activity of such a bis-imidazole varies and is highly dependent on the locations and orientations of the two imidazole rings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation